THE ROLE OF MAGNETIC STELLAR WIND AND MASS TRANSFER IN CLOSE BINARIES OF THE EARLY SPECTRAL TYPE - Perevozkina, E. L (Одеські астрономічні публікації, 2017)
We suggest the results of calculations of mass transfer rate using orbital period changing and changing of orbital semi-major axis due to magnetic stellar Wind and mass transfer in close binaries of early spectral type.